Diphthongized Monophthongs of Acehnese Oral Vowels in Samatiga Dialect - Tanzir Masykar; Febri Nurrahmi; Abdullah Al Mulhim (Journal of Language and Literature, 2021)
Diphthong has been reported as the character of old Acehnese, which is now eroded in some words of modern Acehnese. However, some dialects, such as Daya and Pidie, still retain certain diphthongs in certain Acehnese words. Samatiga dialect is one of the dialects in Aceh Barat. People in Aceh Barat has commonly marked this dialect as producing certain vowel as diphthong similar to those in Teunom and Daya. Thus, the current study aims to explore the diphthongization of certain monophthong in Acehnese words by the people in Samatiga. Specifically, it aims to learn the monophthongs often diphthongized in this dialect, the position in which the diphthong occurs, and the movement trajectory of the diphthong. Two language consultants are consulted to explore their diphthongization, and two other Acehnes are discussed to determine their diphthongization. Their production is recorded using a high-quality recorder and analyzed in Praat to obtains its formants data. The findings indicate that not all monophthongs are produced as diphthongs in Samatiga dialect. Samatiga dialect replaces vowel /ɛ/and /ɔ/ with diphthong /ai/ and /au/. The diphthong /au/ seems to be unique to Samatiga dialect since previous studies did not mention Acehnese diphthong ending in /u/. The diphthongization only occurs when it comes in the word final and open syllable. The diphthong /au/trajectory movement is greater than /ai/, indicating the former, not the initial may experience transformation into monophthong like other major dialects in Aceh.